The effects of acute stress exposure on striatal activity during Pavlovian conditioning with monetary gains and losses - Lewis, Andrea H.; Porcelli, Anthony J.; Delgado, Mauricio R. (Frontiers in Behavioral Neuroscience, 2014)
Pavlovian conditioning involves the association of an inherently neutral stimulus with an appetitive or aversive outcome, such that the neutral stimulus itself acquires reinforcing properties. Across species, this type of learning has been shown to involve subcortical brain regions such as the striatum and the amygdala. It is less clear, however, how the neural circuitry involved in the acquisition of Pavlovian contingencies in humans is affected by acute stress. In the current study, we investigate the effect of acute stress exposure on Pavlovian conditioning using monetary reinforcers. Participants underwent a partial reinforcement conditioning procedure in which neutral stimuli were paired with high and low magnitude monetary gains and losses. A between-subjects design was used, such that half of the participants were exposed to cold stress while the remaining participants were exposed to a no stress control procedure. Cortisol measurements and subjective ratings were used as measures of stress. We observed an interaction between stress, valence and magnitude in the ventral striatum, with the peak in the putamen. More specifically, the stress group exhibited an increased sensitivity to magnitude in the gain domain. This effect was driven by those participants who experienced a larger increase in circulating cortisol levels in response to the stress manipulation. Taken together, these results suggest that acute stress can lead to individual differences in circulating cortisol levels which influence brain regions involved in associative learning such as the ventral striatum.